2010
DOI: 10.1021/ja100236b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable Inverted Polymer Solar Cells Integrated with a Cross-Linked Fullerene Material as an Interlayer

Abstract: A novel PCBM-based n-type material, [6,6]-phenyl-C(61)-butyric styryl dendron ester (PCBSD), functionalized with a dendron containing two styryl groups as thermal cross-linkers, has been rationally designed and easily synthesized. In situ cross-linking of PCBSD was carried out by heating at a low temperature of 160 degrees C for 30 min to generate a robust, adhesive, and solvent-resistant thin film. This cross-linked network enables a sequential active layer to be successfully deposited on top of this interlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
261
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(265 citation statements)
references
References 50 publications
3
261
1
Order By: Relevance
“…82 To rectify one of the problems with PCBM (namely its tendency to undergo excessive crystallization), research has effectively demonstrated the use of cross-linking groups. 83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…82 To rectify one of the problems with PCBM (namely its tendency to undergo excessive crystallization), research has effectively demonstrated the use of cross-linking groups. 83,84 Of similar interest are polymers carrying pendent fullerenes, 85 although they tend to suffer from aggregative effects of C 60 rather than self-assembly, 86 or linear main-chain polymers based on C 60 as a monomer, which seem to have displayed morphologies more appropriate to charge collection and transfer. 87 Further work on other acceptors such as perylene, notably perylene tetracarboxydiimide (PDI), 88,89 the poly(benzimidazobenzophenanthroline) ladder (BBL), 90 and units based on 9,9'-bifluorenylidene, 91 conversely, have shown that fullerene may not be necessary.…”
Section: Figurementioning
confidence: 99%
“…The fiber-based photovoltaic cell, which was a solar collector that utilized internal reflector to confine light into an organic absorber, collected nearly 80% of the incoming photons as current, at ~3 kOhms.cm (Zhou et al, 2009). Li et al (2010) developed a mathematical model that was also supported by experimental results, for light transmission, absorption and loss in fiber-based organic solar cells using ray tracing and optical path iteration. A patent was developed about photovoltaic devices having fiber structure and their applications (Curran et al, 2009).…”
Section: Device Structuresmentioning
confidence: 99%
“…vanadium oxide and cesium carbonate), which are used as buffer layer of inverted polymer solar cells (Li et al, 1997). However, there is still a trade-off between stability and photovoltaic performance in inverted solar cells (Hsieh et al, 2010). Organic solar cells have many advantages such as potential to be semi-transparent, manufacture on both large or small areas compatible with mass production and low-cost, production possibility with continuous coating and printing processes on lightweight and flexible substrates (for example textiles), ecological and low-temperature production possibilities (Dennler et al, 2006a;Dennler & Sariciftci, 2005).…”
Section: Organic Solar Cellsmentioning
confidence: 99%
“…The organic active layer of polymer solar cells typically consists of a p-conjugated polymer donor and a fullerene derivative acceptor, and the power conversion efficiency (PCE) of polymer solar cells has recently achieved 6-8%. This has been driven by the development of new p-conjugated polymers [5][6][7][8] and fullerene derivatives [9,10]. In addition to increasing their efficiency, studies into their commercial viability (e.g.…”
Section: Introductionmentioning
confidence: 99%